Ump getting good tips from UTM on processes and practices involved when applying for research grant - Putra Mohd Darul Ridzuan, Rosli (Penerbit UMP, 2015)

(untitled)
The acculturation of research and knowledge in the development of an institute of knowledge is one of the key elements for researchers. Apart from classroom learning, research is one of the means where knowledge can be nurtured and shared between educators and community.